A 36-Year-Old Male with Snake Bite Grade I Manus Dextra Case Report - Dewi, Ratna; Pranandari, Ayun; Ardani, Yanuar (International Journal of Cell and Biomedical Science, 2024)
Background: Snakebite remains a major global public health concern, particularly in tropical regions like Indonesia. Snake envenomation may lead to local and systemic manifestations including erythema, swelling, pain, hypotension, respiratory distress, and even death. Case: A 34-year-old male presented to the Emergency Department of Esensia Main Clinic with the chief complaint of a traumatic wound on the right hand resembling a snakebite, accompanied by hand swelling, pain, nausea, and dizziness. The patient had applied a cloth bandage prior to arrival. Results: The patient was diagnosed with a grade I snakebite of the right hand (manus dextra) based on clinical history and physical examination. Management included administration of anti-snake venom serum (ASVS). Conclusion: Venomous snakebites can result in severe outcomes, including death; thus, early and appropriate management is crucial. In this case, medical treatment included administration of ASVS.